Peripheral blood progenitor cell (PBPC) counts during steady-state haemopoiesis enable the estimation of the yield of mobilized PBPC after granulocyte colony-stimulating factor supported cytotoxic chemotherapy: an update on 100 patients - Frühauf, Stefan; Schmitt, Karin; Veldwijk, Marlon R.; Topaly, Julian; Benner, Axel; Zeller, W. Jens; Ho, Anthony Dick; Haas, Rainer (British journal of haematology, 1999)
Peripheral blood progenitor cells (PBPC) can be mobilized using chemotherapy and granulocyte colony-stimulating factor (G-CSF). We and others previously reported a correlation of steady-state PBPC counts and the PBPC yield during mobilization in a small group of patients. Here we present data on 100 patients (patients: 25 non-Hodgkin's lymphoma (NHL), five Hodgkin's disease, 35 multiple myeloma (MM), 35 solid tumour) which enabled a detailed analysis of determinants of steady-state PBPC levels and of mobilization efficiency in patient subgroups. Previous irradiation (P = 0.0034) or previous chemotherapy in patients with haematological malignancies (P = 0.0062) led to a depletion of steady-state PB CD34+ cells. A correlation analysis showed steady-state PB CD34+ cells (all patients: r = 0.52, P < 0.0001; NHL patients, r = 0.69, P = 0.0003; MM patients: r = 0.66, P = 0.0001) and PB colony-forming cells can reliably assess the CD34+ cell yield in mobilized PB. In patients with solid tumour a similar trend was observed in mobilization after the first chemotherapy cycle (r = 0.51, P = 0.05) but not if mobilization occurred after the second or further cycle of a sequential dose-intensified G-CSF-supported chemotherapy regimen, when premobilization CD34+ counts were 18-fold elevated (P = 0.004). When the patients with MM (r = 0.63, P = 0.0008) or with NHL (r = 0.65, P = 0.006) were analysed separately, a highly significant correlation of the steady-state PB CD34+ cell count to the mean leukapheresis CD34+ cell yield was found, whereas no correlation was observed for patients with a solid tumour. For patients with haematological malignancies estimates could be calculated which, at a specific steady-state PB CD34+ cell count, could predict with a 95% probability a defined minimum progenitor cell yield. These results enable recognition of patients who mobilize PBPC poorly and may assist selection of patients for novel mobilization regimens.